Measuring expectation for an affordance gap on a smartphone user interface and its usage among older adults - Wong, Chui Yin; Ibrahim, Rahimah; Hamid, Tengku Aizan; Mansor, Evi Indriasari (ProQuest, 2020)
The smartphone has become a ubiquitous mobile communication tool that plays a crucial role in the daily lives for Malaysian older adults. However, it is not easy for older adults to learn new interaction modes and adopt the smartphone user interface. In this paper, we aim to examine the affordances of a smartphone user interface and its usage by older adults through the lens of Norman’s execution/evaluation action cycle (EEAC) framework. A mobile-user interaction study was administered with four tasks. A paired sample t-test was conducted to analyze the affordance gap between different levels of expectation. The results revealed that three tasks (making phone calls, adding contacts, and using WhatsApp) were statistically different; the exception was installing mobile apps. The results underscore the importance of mobile apps designers incorporating older adults’ needs and expectations as a means to reduce the affordance gap.